Development of Instant Feed Recipe for Blood Worm Culture - Sriin, Amonsri (Journal of Advanced Development in Engineering and Science, 2023)
The objectives of this research were 1) to study the appropriate Instant feed Recipe for BloodWorm Culture and 2) to study the efficiency of instant feed recipe for blood worm culture. The appropriate instant feed recipe for blood worm culture was developed from 4 recipes: 1) pig feed, 2) pig feed and clay, 3) pig feed and EM and 4) pig feed, clay and EM. The results showed that the 4th recipe gave the highest yield that was average weight of blood worm 3.98 grams with the 2th, 3th and 1th recipe following that the average weight of blood worm were 1.99, 1.87, and 0.16 grams, respectively. The blood worm fed by the different recipes showed the significantly different yield (P<0.05). After the 4th recipe containing pig feed, clay and EM was used to produce instant feed recipe for blood worm culture; the efficiency of 4th recipe was non-significant difference with instant feed recipe for blood worm culture (P>0.05)